DISCRETE MODELING OF TECTONIC COATINGS OF ARCHITECTURAL BUILDINGS IN THE APPEARANCE OF A TRIANGULATION GRID - Мостовенко, Олексій; Ковальов, Сергій; Мостовенко, Олександр (Modern engineering and innovative technologies, 2024)
In this study, the formation of a discrete model of a momentless tectonic covering of constant thickness with a constant section of supporting arches on a triangulation grid is considered. The external load on the nodes of the discrete model of the momen